2021
DOI: 10.1002/anie.202110091
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surfactants on the Molecular Structure of the Buried Oil/Water Interface

Abstract: The oil/water interface,for instance in emulsions,is often stabilized by surfactants.H ence,t he co-existence of oil, water,and surfactant molecules at the buried oil/water interface determines macroscopic properties such as surface tension or emulsion stability.U tilizing an inherently surface sensitive spectroscopic method, sum frequency generation (SFG) spectroscopy, we showt hat adsorption of an anionic surfactant to the buried oil/water interface increases the magnitude of the interfacial electric field. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 50 publications
1
23
0
Order By: Relevance
“…28 The signal contribution of the dispersive term in the organic regime is significantly smaller than that of the adsorptive term, and hence, the dispersive term has been usually ignored in the literature. 31 The coincidence of the input IR frequency with one of the molecular vibrations results in an apparent increase in χ eff,R (2) and the SFG signal. Hence, probing the IR through a frequency range produces a vibrational spectrum of the interfacial molecules.…”
Section: Ir Vis Vismentioning
confidence: 99%
See 1 more Smart Citation
“…28 The signal contribution of the dispersive term in the organic regime is significantly smaller than that of the adsorptive term, and hence, the dispersive term has been usually ignored in the literature. 31 The coincidence of the input IR frequency with one of the molecular vibrations results in an apparent increase in χ eff,R (2) and the SFG signal. Hence, probing the IR through a frequency range produces a vibrational spectrum of the interfacial molecules.…”
Section: Ir Vis Vismentioning
confidence: 99%
“…As the surfactant concentration at the interface is much higher than that in the diffuse layer, the χ (3) contributions to the SFG signals obtained in the organic range (from 2800 to 3000 cm –1 ) can be assumed purely real . The signal contribution of the dispersive term in the organic regime is significantly smaller than that of the adsorptive term, and hence, the dispersive term has been usually ignored in the literature …”
Section: Sum-frequency Generation Spectroscopymentioning
confidence: 99%
“…The SDS–water interface has also been probed previously using spectroscopic techniques over a broad frequency range. 30 32 These studies showed that the negative charge of the amphiphilic DS – ion induces an extended orientation of the water molecules in the vicinity of the water surface. However, how the mixed surfactant systems alter the surface electric field remains quite an unexplored topic.…”
mentioning
confidence: 99%
“…In this study, it was found that C 12 E 6 at CMC (70 μm) generates a strong electric field of 1 V/nm arising from the orientational structure of both the hydrophobic and hydrophilic parts of the surfactant and water molecules. The SDS–water interface has also been probed previously using spectroscopic techniques over a broad frequency range. These studies showed that the negative charge of the amphiphilic DS – ion induces an extended orientation of the water molecules in the vicinity of the water surface. However, how the mixed surfactant systems alter the surface electric field remains quite an unexplored topic.…”
mentioning
confidence: 99%
“…Although the knowledge of the interfacial molecular structure and the charging state in emulsions is of great importance, most of the existing knowledge arises from experimental data of extended o/w interfaces because they can be more easily accessed with a large variety of complementary methods such as surface tensiometry, , ellipsometry, and nonlinear optical spectroscopy as well as with theoretical simulations. , The results from extended o/w can explain reasonably well the behavior of macroemulsions since the curvature of the droplet is large enough compared to molecular dimensions and to the relevant Debye lengths of interfacial double layers when charged oil droplets are considered. That is because in the large particle limit, the electric double layer can be still treated as if an extended interface would be present.…”
mentioning
confidence: 99%